The Influence of Discipline and Learning Environment on the Learning Achievement of Student in Class VIII Subject IPS Subject Matter of Social Deviation at SMPK Yos Soedarso Ende - Elias Beda (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to determine and describe; (1) The effect of learning discipline on the learning achievement of VIII grade students of social studies subject matter of social deviation at Yos Sudarso Ende Junior High School, (2) The effect of learning environment on the learning achievement of VIII grade students of social studies subject matter of social deviation at Yos Sudarso Ende Junior High School, (3) The effect of learning discipline and learning environment on the learning achievement of VIII grade students of social studies subject matter of social deviation at Yos Sudarso Ende Junior High School. This type of research is quantitative research. The main data collection techniques; (1) Questionnaire (2) Test, and (3) (Documentation). The data collected was analyzed using the double correlation formula produced by the moment model Sugiyono. The results showed that: (1) There is a correlation between the achievement variable and the learning environment with the learning discipline control variable obtained a relationship of 0.546 (strong) with a sig probability of 0.000, meaning that the relationship is significant. The calculation results show that the t value for the interpretation coefficient for β0 = 0.615 provides a significant value at α = 0.05 (it can be seen that the t value = 5.349 with 59 degrees of freedom is greater than t table = 2.576 or Sig = 0.000); for β1 = 0.438 provides a significant value at α = 0.05 (it can be seen that the t value = 3.863 with 59 degrees of freedom is greater than t table = 2.576 or Sig = 0.000), meaning that learning achievement can be influenced by learning discipline by 0.438 (meaning that if learning discipline increases by 1% it will affect the increase in learning achievement by 0.437%, if the learning environment is constant), (2) There is an influence of the learning environment on the learning achievement of social studies students in class VIII SMPK Yos Sudarso Ende). Likewise, learning achievement can be influenced by the learning environment by 0.481 (meaning that if the learning environment increases by 1%, it will affect the increase in learning achievement by 0.481%, if the learning discipline is constant). Thus it can be suggested, (1) To the School. It is recommended that the school pay attention to the student learning environment because the results of the study prove that there is a significant influence between learning achievement and the learning environment, (2) To Parents. Parents of students are advised to create a conducive learning environment for children at home so that children can learn well.